Developments in the economics of privatization and regulation - Crew, Michael A.; Parker, David, 1949 Sept. 28- (Cheltenham, Glos, UK ; Northampton, MA : Edward Elgar, 2008)
This book brings together a collection of previously published papers on privatization and regulation that have had an impact on the thinking of economists, policymakers and civil servants.
Includes bibliographical references and index.
uaj 23/05/2013
Loans
Keywords: Privatization -- Economic aspects; Trade regulation -- Economic aspects